Morphology and ultrastructure of Brachymystax lenok tsinlingensis spermatozoa by scanning and transmission electron microscopy - Guo, Wei; Shao, Jian; Li, Ping; Wu, Jinming; Wei, Qiwei (Tissue & cell, 2016)
This study was conducted to investigate Brachymystax lenok tsinlingensis spermatozoa cell morphology and ultrastructure through scanning and transmission electron microscopy. Findings revealed that the spermatozoa can be differentiated into three major parts: a spherical head without an acrosome, a short mid-piece, and a long, cylindrical flagellum. The mean length of the spermatozoa was 36.11±2.84μm, with a spherical head length of 2.78±0.31μm. The mean anterior and posterior head widths were 2.20±0.42μm and 2.55±0.53μm, respectively. The nuclear fossa was positioned at the base of the nucleus that contained the anterior portion of flagellum and a centriolar complex (proximal and distal centrioles). The short mid-piece was located laterally to the nucleus and possessed just one spherical mitochondrion with a mean diameter of 0.65±0.14μm. The spermatozoa flagellum was long and cylindrical, and could be separated into two parts: a long main-piece and a short end-piece. The main piece of the flagellum had short irregular side-fins. The axoneme composed the typical '9+2' microtubular doublet structure and was enclosed by the cell membran e. This study confirmed that B. lenok tsinlingensis spermatozoa can be categorized as teleostean "Type I" spermatozoa; 'primitive' or 'ect-aquasperm type' spermatozoa. To the best of the authers knowledge, this was the first study conducted on the morphology and ultrastructure of B. lenok tsinlingensis spermatozoa.
Keywords: Mitochondria; Acrosome; axonema; flagella; spermie; Salmonidae; Cell Nucleus; Flagella; Transmission electron microscopy; Microscopy, Electron, Scanning; buněčné jádro; mitochondrie; Centrioles; Axoneme; zvířata; akrozom; Ultrastructure; Brachymystax lenok tsinlingensis; Male; mikroskopie elektronová rastrovací; Scanning electron microscopy; Morphology; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Spermatozoa; Animals; mužské pohlaví; centrioly